Novel Pathogenic PRSS1 Variant p.Glu190Lys in a Case of Chronic Pancreatitis - Jancsó, Zsanett; Oracz, Grzegorz; Kujko, Aleksandra Anna; Kolodziejczyk, Eliwira; Radisky, Evette S.; Rygiel, Agnieszka Magdalena; Sahin-Tóth, Miklós (Frontiers in Genetics, 2019)
Mutations in the PRSS1 (serine protease 1) gene encoding human cationic trypsinogen cause hereditary pancreatitis or may be associated with sporadic chronic pancreatitis. The mutations exert their pathogenic effect either by increasing intra-pancreatic trypsinogen activation (trypsin pathway) or by causing proenzyme misfolding and endoplasmic reticulum stress (misfolding pathway). Here we report a novel heterozygous c.568G>A (p.Glu190Lys) variant identified in a case with chronic pancreatitis. The parents of the index patient had no history of pancreatitis but were unavailable for genetic testing. Functional characterization revealed 2.5-fold increased autoactivation of the mutant trypsinogen relative to wild type. Unlike many other clinically relevant PRSS1 mutations, p.Glu190Lys did not alter the chymotrypsin C (CTRC)-dependent degradation of trypsinogen nor did it increase CTRC-mediated processing of the trypsinogen activation peptide. Cellular secretion of the mutant protein was unchanged indicating normal folding behavior. Based on the genetic and functional evidence, we classify the p.Glu190Lys PRSS1 variant as likely pathogenic, which stimulates autoactivation of cationic trypsinogen independently of CTRC.